Workers' Wage Payment Information System Using the Scrum Method - Gulo, Yeskarwani; Safitri, Andin Eka; Sari, Willis Puspita (LPPM Institut Pendidikan Nusantara Global, 2025)
Employees receive routine services and compensation in the form of salaries as part of their work performance through company operations. However, several companies still rely on manual payroll processing, including those that participated in a recent business exhibition. One such company continues to use Microsoft Office applications to manage payroll data manually. This outdated method significantly slows down the process of generating employee payslips and frequently leads to calculation errors in employee compensation. Furthermore, the Human Resources Department (HRD) is required to manually verify all data before integrating the final salaries of permanent employees into the monthly payroll report. This process is not only time-consuming but also increases the risk of human error and administrative inefficiency. As a response to these challenges, the company developed a web-based employee compensation information system. This system is designed to automate the entire payroll process, from attendance tracking and allowance calculation to deductions and payslip generation. With simultaneous salary data entry and report generation, the system improves business performance, enhances accuracy, and reduces processing time. The final outcome of this study is an automated payroll system that adheres to predefined business rules and allows for easy future updates. Most importantly, it helps reduce human error in payroll calculations by up to 60%, offering a more efficient and reliable payroll management solution.